Observations on the Utility of the Semi-directive Interview for Documenting Traditional Ecological Knowledge - Huntington, Henry P. (ARCTIC, 1998)
Traditional ecological knowledge (TEK) offers ecological information and insight relevant to ecological management and research that cannot be obtained from other sources. Its use is hindered by difficulties of access, in that TEK is typically not available to a wide audience. Documentation can overcome this obstacle, allowing TEK to be considered with other forms of easily disseminated information. This paper describes the author's experience using the semi-directive interview to document TEK about beluga whales in Alaska. This method allows the participants as well as the researcher to guide the interview, so that associations made by the participant, and not just those anticipated by the researcher, are discussed. Using maps as the starting point for discussions with individuals or groups, the interviews covered expected topics, such as migration and feeding behavior, as well as unanticipated topics, such as the possible influence of beavers on beluga distribution. The primary research session was followed a year later by a review session to verify the accuracy of the draft report, add missing information, or remove information the publication of which might harm community interests. The author found the semi-directive interview to be an effective and powerful method for accurate and comprehensive documentation of TEK. It worked especially well in group interviews, which allowed participants to stimulate and validate each other. Le savoir écologique traditionnel (SET) offre de l'information écologique et une opinion pertinente à la gestion et à la recherche écologiques qu'on ne peut obtenir d'autres sources. Un accès difficile gêne l'utilisation du SET, vu qu'en général il n'est pas disponible à un vaste public. On peut surmonter cet obstacle en créant de la documentation, ce qui permet de tenir compte du SET parallèlement à d'autres formes d'information facilement diffusée. Cet article décrit l'expérience de l'auteur qui s'est servi de l'interview semi-dirigée pour documenter le SET sur les bélougas de ...